Recognizing immunodeficiency in children with recurrent infections: What are the predictive factors? - Sütçü, Murat; Acar, Manolya; Aktürk, Hacer; Hançerli-Törün, Selda; Salman, Nuran; Somer, Ayper (The Turkish Journal of Pediatrics, 2016)
The aim of this study was to evaluate the children presenting with the complaint of recurrent infections and to determine the possible predictive factors foreseeing the requirement for further investigations. Turk J Pediatr 2016; 58: 609-615. This study is a retrospective analysis of 507 children (221 female, 43.6%) with median age of 46 (range 4-190) months, who attended our department with the complaint of recurrent infections between January 2013 and December 2014 during two years period. The majority of the patients were preschool age children (n: 360, 71%). Most of the infections were upper repiratory tract infections [URTI (n: 380, 75%)]. The patients were divided into 4 diagnostic groups; as atopic children (n: 148, 29.2%), children with primary immune deficiency [PID (n: 54, 10.7%)], patients with chronic disorders (n: 40, 7.9%) and the majority, healthy subjects (n: 265, 52.3%). Among school age patients, the incidence of atopic children was significantly high (p: 0.016). Presenting at adolescent age group, growth retardation and hypogammaglobulinemia were the predictive risk factors for PID. Antibody (B cell) deficiencies (n: 43, 80%), and among those, selective IgA deficiency (n: 23, 4.5%) constituted the majority of the patients in PID. Rheumatological diseases (n: 9, 1.8%), mainly periodic fever syndromes, were the most common chronic disorders. Malignancy (acute lymphoblastic leukemia and lymphoma) was obtained in two patients (0.4%). Complaint of recurrent infections is very common among children attending health care facilities. It is crucial for clinicians to differentiate the children who need further investigations, urgent medical attention.
Keywords: children; immunodeficiency; recurrent infections